A Comparative Study on Effect of IFRS on Profitability of Selected Companies in Developed and Developing Countries - Sharma, Pooja; Gupta, Sushant (Indian Journal of Finance, 2019)
The new accounting standards aim to provide a worldwide framework for preparing and presenting the financial statements for the stakeholders of business, faithful presentation, objectivity, and relevance for users. These new reporting standards may or may not give the effect on profitability of the concerns. Therefore, the present study was conducted to examine the effect of IFRS on profitability position of IFRS adopted companies with special reference to developed and developing countries. The sample for the purpose of the present study consisted of a total of 29 companies of selected developed countries and 27 companies of selected developing countries. The collected data were time series as well as cross section. Consequently, the study applied panel data technique for the purpose of analysis. Further, the findings showed that IFRS had a significant impact on profitability of the concerns, but there was no significant difference in the profits of IFRS adopted companies of developed countries and developing countries.